Analysis of the impact of sea sand mining on coastal communities of Aeng Batu Batu Sub-District, Galesong Utara, Takalar District (Case study of sea sand mining PT. Gasing Sulawesi) - Lukman Daris; Asriandi Asriandi; Irwansyah Irwansyah; Arifandi Arifandi (Sangia Research Media and Publishing, 2023)
Makassar City is one of the cities in Indonesia, with a large population and rapid economic activity with office buildings, settlements, industry, ports and other facilities such as trade, entertainment and tourism centres. This has attracted attention due to the need for more land to support the growth and development of the City area. One way to create new space in beach reclamation. The local government utilizes the coastal area to carry out various activities. One of the areas adjacent to Makassar City, which is used as mining for reclamation, is North Galesong District, Takalar Regency. Dredging sand for reclamation creates social conflict for the people of North Galesong. Excessive and uncontrolled use of sea sand can damage its carrying capacity. In addition to environmental impacts, socio-economic impacts are a significant problem in areas affected by sand mining and carried out by business people and the government in supporting the development of the Center Point of Indonesia CPI and New Port. Responding to these problems, this study aims to analyze the impact of sea sand mining on the socio-economic community of Aeng Batu-Batu Village, North Galesong District, Takalar Regency. The research method used is a case study investigating various phenomena. The population in this study is related to and directly impacts sea sand mining with a sampling technique, namely Non Purposive Sampling. The survey results show that sand mining activities in Aeng Batu Batu Village, North Galesong District, Takalar Regency have a socio-economic impact on the local community, which has a very significant impact on the conditions before and after sea sand mining activities. These impacts are: 1) Disturbing the activities of small fishermen, namely by the back and forth and the activities of sea sand mining companies. 2) Reducing the catch of fishing line and gill net fishermen by up to 80%. 3) Disturbing fishing operations, namely by disturbing the target habitat of fishermen. 4) Disturbing the fishing area so that the fishing ground changes, which results in increased operational costs.